FAMILY NURSING CARE IN CASE OF GOUT ARTHRITIS WITH NURSING DIAGNOSIS OF ACUTE PAIN IN SIDOGEMBUL VILLAGE, SUKODADI DISTRICT, LAMONGAN REGENCY - Iswatun, Iswatun; Wijayanti, Endah sri; Umam, Khotibul; Susanto, Joko; Kartika, Aprilia Ayu; Lutfiandini, Cherlys Tin (Universitas Airlangga, 2023)
Introduction: Since the end of 2019, the COVID-19 virus has turned into a global health problem and has changed various aspects of life, including education. The government felt compelled to close down the school and encouraged students to carry out online learning. During the online learning process, there are numerous arising obstacles. Thus, the government considered changing it to offline learning in 2021. In its implementation, however, there were many factors regarding learning readiness that must be taken into account, such as physical, psychological, and material readiness. This study aims to analyze the factors influencing offline learning readiness during the COVID-19 pandemic. Methods: This study is quantitative research carried out by employing a cross-sectional approach. There were 49 respondents obtained through a total sampling technique. A questionnaire was utilized as the research instrument and the Chi-Square test was used as the bivariate data analysis. Results: The result revealed that most respondents (73.5%) were females and the mean value of respondents' age was 20.88 years. Furthermore, the respondents had high offline learning readiness (67.3%) and physical readiness, psychological readiness, and material readiness classified under the